Preparation of Polyaniline Emeraldine Salt for Conducting-Polymer-Activated Counter Electrode in Dye Sensitized Solar Cell (DSSC) using Rapid-Mixing Polymerization at Various Temperature - Auliya Nur Amalina; Muhammad Reza; Phutri Milana; Damar Rastri Adhika; Viny Veronika Tanuwijaya; Veinardi Suendo; Risa Rahmawati Sunarya (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Polyaniline Emeraldine Salt (PANI ES) as a conductive polymer has been used as a Pt-free counter electrode materials in DSSC. In this study, polymerization temperature was varied at relatively high temperature from 308 to 348 K with respect to the standard low polymerization temperature at 273 K. The synthesis held in varied high-temperature to study the effect of synthesis condition resulted to the performance as counter electrode in DSSC. The effect of high-temperature synthesis condition gives interesting results, the FTIR-ATR spectra show the presence of vibrational modes of phenazine structure obtained at high polymerization temperature, indicate the changing in the chain geometry. Raman Spectroscopy shows the decrease of the I1194/I1623 intensity ratio that can be interpreted that the degree-of-freedom of C-H bond bending mode decreases in the benzenoid ring, while the stretching mode degree-of-freedom along the chain is preserved or increased. The electrical conductivity profile has changed from metal-like at low-temperature into a semiconductor-like profile at high-temperature. Scanning Electron Microscope images reveals that a change in the morphology of PANI ES with temperature. At low-temperature (273 K) the morphology has a globular shape, while at high-temperature it tends to form nanorod structure. DSSC device with highest efficiency is attained for PANI ES polymerized at 273 K (1.91%) due to its high conductivity. The lowest efficiency is observed in device using PANI ES synthesized at 328 K (1.15%) due to its low conductivity due to the formation of phenazine structure.